Skrining Fitokimia Ekstrak Duri Landak Laut Api (Heterocentrotus Mamillatus) sebagai Antimikroba - Rosdarni, Rosdarni (Jurnal Ilmu Medis Indonesia, 2022)
Purpose: To determine the content of secondary metabolites in the spines of the fire sea urchin (Heterocentrotus mammilatus) as an antimicrobial agent. Method: This type of research is a quasi-laboratory experiment by taking samples of fire sea urchins, conducting phytochemical screening methods to determine the content of chemical compounds, and methods of extracting fire sea urchins with ethyl acetate solvent and testing antimicrobial properties against Escherichia coli. Results: Screening phytochemicals found in the spines of the fire sea urchin are alkaloids, flavonoids and glycosides. Fire sea urchin thorn extract has antimicrobial activity against E.coli of 5.5 mm. Limitations: Further research needs to be done on the content of primary metabolites present in sea urchins and their gonads Contribution: To avoid the level of extinction of the sea urchin species, the local government, especially North Buton Regency, needs to monitor the use that is not controlled by the local community.